ANALISIS DAMPAK COVID-19 PADA LAPORAN LABA RUGI - Fitri; Sri Angraeni; Anita Achmad Payu; Shinta Aulia Maharani Sarif; Muhammad Ramandha Shiddiq (JURNAL LENTERA BISNIS, 2024)
The Covid-19 pandemic has had a significant impact on various aspects of life, including the economy and industries in Indonesia. This impact is reflected in the profit and loss statements, which are important indicators in understanding a company's financial performance. This research aims to analyze the profit and loss statements of PT. Mayora Indah Tbk. from 2018 to 2022, with a focus on how the Covid-19 pandemic has affected the company's financial performance. The research method used in this study is descriptive analysis, using secondary data from the company's profit and loss statements during the period. The results of the analysis show that the company experienced various changes in financial performance during the 2018-2022 period, as a response to the challenging economic conditions caused by the pandemic. Although there was a decline in performance in 2021, the company was able to overcome the negative impact and achieve positive growth in 2022. This analysis provides a comprehensive understanding of PT. Mayora Indah Tbk.'s adaptability and success in facing economic and market challenges during the Covid-19 pandemic. This research provides important insights into how leading manufacturing companies like PT. Mayora Indah Tbk. can survive and grow amidst the uncertain business and economic landscape caused by the global pandemic.